L’étendue du débat public - Gilles Gauthier (Communication, 2021)
The author presents a formal framework for analyzing the structure of public debate. That debate is not limited to its most flagrantly obvious ins and outs. The author identifies three types of subdebate that can be associated with a central debate and determine its structure and the way it unfolds: infra‑debates, para‑debates, and meta‑debates. Drawing on public debates in Québec, he shows that the three do not all have the same relationship to the central debate and thus do not have the same effect.